War Powers Resolution : Fifteen Years of Experience. (U.S. Congressional Research., 1988)
Examines provisions of the War Powers Resolution, Supreme Court decision against legislative veto, reporting requirements, congressional consultation, and proposed amendments. Also considers cases of military intervention in El Salvador, Honduras, Lebanon, Libya, and the Persian Gulf.